PENINGKATAN KOMPETENSI KEPALA SEKOLAH MELALUI DIKLAT PENGUATAN - Husni Hamdani (Jurnal Tata Kelola Pendidikan, 2021)
The assignment of teachers as school principals is stipulated in Permendikbud Number 6 of 2018. One of the points is that school principals who are wearing and do not have a certificate of completion of the training, prospective school principals are required to attend and pass training to strengthen school principals. This training is also to develop attitudes, knowledge, skills in the dimensions of personality, managerial, entrepreneurship, supervision, and social, according to the Regulation of the Indonesian Minister of Education Regulation Number 13 of 2007 concerning the standards of school / madrasah principals. The main objective of this study is to obtain significant differences in the competence of school principals before and after participating in strengthening training. The method used in this research is descriptive method with a quantitative approach using ex post facto that explores an event that has occurred. The sample used was all school principals who had participated in strengthening training as many as 41 people at elementary schools in Cikancung District. The data technique used a questionnaire method and documentation study. The results of the calculation of the Average Weight Score (WMS) show that the competence of the principal before the training received a score of 3.53, including the high category, and the competence of the principal before the training received a score of 4.41 which was in the very high category. The results of the normality test on the data distribution show that the principal's competency variables are normally distributed. Analysis of comparative data using Paired Sample T Test, obtained an average score of competence before training 125.7073, while after training strengthening 158.2683. Then the test results obtained ????count 15.551 ???????????????????????? 2.021, which is a significant difference in the competence of school principals before and after participating in strengthening training.